Lhcf2 in the peripheral antenna is essential for nonphotochemical quenching and Lhcx1 accumulation in the diatom Chaetoceros gracilis - Jian Xing; Minoru Kumazawa; Kentaro Ifuku (Proceedings of the National Academy of Sciences, 2026)
Photosynthetic organisms must continuously balance efficient light harvesting with protection against excess excitation energy, a challenge met by nonphotochemical quenching (NPQ). Although the molecular components involved in NPQ have been extensively studied, how the essential energy-quenching site is assembled remains poorly understood, particularly in marine diatoms. Here, we show that in the centric diatom Chaetoceros gracilis , which belongs to one of the most abundant and diverse genera in marine phytoplankton, the light-harvesting complex (LHC) protein Lhcf2 is required for energy-dependent quenching (qE). Targeted knockout of Lhcf2 abolished qE by preventing the stable accumulation of Lhcx1, a core component of the NPQ effectors in this species. Lhcf2 localizes to the peripheral antenna system and associates with Lhcx1 in a higher-order complex suggested by biochemical and functional analyses. In contrast, other established NPQ-related factors, including the trans-thylakoid proton gradient and the accumulation of diatoxanthin, were not affected by the loss of Lhcf2. These results identify a non-Lhcx-type LHC protein as an essential structural component for qE-NPQ and establish a general design principle for the cooperative assembly of photoprotective energy-quenching sites in eukaryotic photosynthesis, with implications for marine carbon fixation.